Firm dynamics and job creation in the United Kingdom: 1998–2013. (February 2015) - Anyadike-Danes, Michael; Hart, Mark; Du, Jun
This article is motivated by a very simple question – 'what types of firms create the most jobs in the UK economy?' One popular answer to this question has been High-Growth Firms (HGFs). These firms represent only a small minority – the 'Vital 6%' – of the UK business population yet, but have a disproportionate impact on job creation and innovation. We re-visit the discussion launched by the 2009 National Endowment for Science, Technology and the Arts (NESTA) reports, which identified the 6% figure and, using more recent data, confirm the headline conclusion for job creation: a small number of job-creating firms (mostly small firms) are responsible for a significant amount of net job creation in the United Kingdom. Adopting our alternative preferred analytical approach, which involves tracking the growth performance of cohorts of start-ups confirms this conclusion; however, we find an even smaller number of job-creating firms are responsible for a very significant proportion of job creation. We conclude by considering the question – 'what are the implications for policy choices?'